Islam and Human Rights in Indonesia: An Account of Muslim Intellectuals’ Views - Fuad, Ahmad Nur; Arbaiyah, A.; Mughni, Syafiq; Jainuri, Achmad (Al-Jami'ah: Journal of Islamic Studies, 2007)
The issue of Islam and human rights has become important issue in Indonesia at least since the last two decades. Indonesian Muslims have developed two different approaches to human rights: in complete agreement with the declaration of universal human rights; and in resistance to that declaration and developing understanding that Islam encompasses human rights values. The article argues for its part that human rights are not absolutely universal, because they are based chiefly on Western values, structures, ethics and morality. For that, it is reasonable to question their universality. The present article focuses on how Indonesian Muslim intellectuals conceive of human rights and Islamic values as they perceive the two. Specifically, it focuses on four principal issues in human rights discourse: freedom of opinion, religious freedoms, rights of women, and criminal law. The authors reveal in the conclusion that although some Indonesian Muslim intellectuals admit that universal human rights are truly universal, they still see differences in certain cases, due to differences in socio-cultural background. They have tried to affect a synthesis between the universality and particularity of both Islamic and universal human rights in order to make both fit within the Indonesian context.